Detection and Quantification of Rhodamine B in Loose Powder and Blush Cosmetic Products - Munthe, Herlina; Sartika Daulay, Anny; Ridwanto, Ridwanto; Munandar Nasution, Haris (Jurusan Farmasi Universitas Negeri Gorontalo, 2025)
The use of decorative cosmetics such as loose powder and blush is increasingly widespread, raising concerns regarding the safety of the coloring agents used, particularly Rhodamine B. This study aimed to identify the presence and determine the levels of Rhodamine B in loose powder and blush cosmetic products using Thin Layer Chromatography (TLC) for qualitative analysis and High-Performance Liquid Chromatography (HPLC) for quantitative analysis. The HPLC method applied in this study was validated and showed good linearity, precision, and sensitivity in accordance with ICH guidelines. A total of 16 cosmetic samples were analyzed, and 3 samples were confirmed to contain Rhodamine B. The highest Rhodamine B level was found in sample X at 66.54 µg/g, followed by sample Z at 21.03 µg/g, and sample Y at 0.83 µg/g. These findings indicate that the presence of Rhodamine B in cosmetic products remains a concern. Therefore, it is necessary to strengthen regulatory supervision and increase public awareness to select safe cosmetic products that are officially registered by BPOM.